Lone Mothers Between Paid Work and Care: The Policy Regime in Twenty Countries : the Policy Regime in Twenty Countries - Kilkey, Majella (Routledge Revivals, 2018)
"This title was first published in 2000. This is a study which compares and contrasts how lone mothers' relationships to paid work and care-giving are constructed across 20 countries, and with what outcomes for lone mothers' levels of economic well-being. In doing so, the book explores from an international perspective, the implications of the re-orientation of lone mothers' citizenship within the UK policy field from that of care-giver to paid worker. The volume engages with feminist comparative social policy literature concerned with specifying a construction of citizenship appropriate to capturing international variations in women's social rights. By incorporating social rights attached to paid work and care, as well as those which enable lone mothers to move between sequential periods of paid work and care-giving across the child-rearing cycle, the study makes a significant contribution to the literature."--Provided by publisher.